Ten invertebrates new for the marine fauna of Madeira. - Wirtz, Peter (2008)
The nemertine Drepanogigas albolineatus, the gastropods Coralliophila kaofitorum, Haminoea orteai, Discodoris rosi and Janolus n sp, the decapod Palaemonella atlantica, the phoronids Phoronis australis and Phoronopsis californica, the starfish Chaetaster longipes and the tunicate Distaplia corolla are recorded from Madeira archipelago for the first time.